Skin-to-skin contact in the delivery room for very preterm infants: a randomised clinical trial - Karoline Aker; Ragnhild Støen; Laila Kristoffersen; Håkon Bergseng; Helene Engesland; Anne Bagstevold (BMJ Publishing Group, 2023)
Objective Evaluating safety, feasibility and effects on physiological parameters of skin-to-skin contact (SSC) from birth between mothers and very preterm infants in a high-income setting.Design Open-label randomised controlled trial.Setting Three Norwegian neonatal units.Patients Preterm infants at gestational age (GA) 280-316 weeks and birth weight >1000g delivered vaginally or by caesarean section (C-section).Intervention Two hours of early SSC between the mother and the infant compared to standard care (SC) where the infant is separated from the mother and transferred to the neonatal unit in an incubator.Results 108 infants (63% male, 57% C-section, mean (SD) GA 30.3 weeks (1.3) and birth weight 1437 g (260)) were included. Median (IQR) age at randomisation was 23 min (17-30). During the first 2 hours after randomisation, 4% (2 of 51) and 7% (4 of 57) were hypothermic (<36.0°C) in the SSC and SC group, respectively (p=0.68, OR 0.5, 95% CI 0.1 to 3.1). Significantly fewer infants in the SSC group had hyperthermia (>37.5°C) (26% (13 of 57) vs 47% (27 of 51), respectively, p=0.02, OR 0.4, 95% CI 0.2 to 0.9). No infant needed mechanical ventilation within the first 2 hours. Median (IQR) duration of SSC was 120 (80-120) min in the intervention group. There was no difference in heart rate, respiratory rate and oxygen saturation between groups during the first 24 hours.Conclusion This study from a high-income setting confirmed that SSC from birth for very preterm infants was safe and feasible. Physiological parameters were not affected by the intervention. The long-term effects on neurodevelopment, maternal-infant bonding and maternal mental health will be collected.Trial registration number NCT02024854.